Reliability of the Patient and Observer Scar Assessment Scale and a 4‐point scale in evaluating linear facial surgical scars. (21st July 2016) - Liu, X.; Nelemans, P.J.; Van Winden, M.; Kelleners‐Smeets, N.W.J.; Mosterd, K.
Abstract: Background: In order to evaluate and improve aesthetic outcome for patients undergoing dermatological surgery, a reliable evaluation tool must be used. The 4‐point scale and the Patient and Observer Scar Assessment Scale (POSAS) were both developed for this purpose. Objective: To compare the reliability of the POSAS scale with the 4‐point scale for facial linear surgical scars and to assess the influence of different scar characteristics on the overall impression. Methods: Patients visiting the outpatient clinics of the Maastricht University Medical Centre with linear facial scars were included. The 4‐point scale and the Observer Scar Assessment Scale (OSAS) were completed by three independent observers. The Patient Scar Assessment Scale (PSAS) was completed by the patient on the day of the visit and 2 weeks later. The intra‐class correlation coefficient (ICC) with corresponding 95% confidence intervals (CI) were calculated to assess the reliability of the scales. Linear multivariate regression analyses were performed to evaluate how the score on each aspect affected the overall opinion. Results: Fifty scars in 50 patients were included. The ICC of the 4‐point scale was 0.819 (95% CI: 0.708–0.892) for multiple observers and 0.602 (95% CI: 0.447–0.734) for single observer. These were superior to the ICCs of total OSAS scores (0.783 95% CI: 0.547–0.888 for multiple observers and 0.546 95% CI: 0.287–0.726 for single observer). ICCs of individual sub‐items on the OSAS scored even lower. The sub‐items contributed differently to the overall opinion among the different observers or patient. Conclusion: In terms of reliability, the overall opinion and the 4‐point scale were superior to the total POSAS score or the sub‐items. Observers do not weight individual scar characteristics equally to arrive at an overall opinion, which challenges the assumption that calculating a total POSAS score by summing of the scores on the individual items is a valid approach.